CPA Examination: Accounting Practice. - Chamberlain, John H. (The Accounting Review, 1966)
The article presents problems and their solutions prepared by the Board of Examiners of the American Institute of Certified Public Accountants, and presented as the first half of the Certified Public Accountants examination in accounting practice held on November 03, 1965. The first question deals with the taxable income of an employee who died, and the liability of his employer towards his widow. The second question deals with the accounting of merger of a proprietorship. Certain questions deal with the issue of calculation of earnings per share. One question deals with the issue of accounting of wages and salaries of employees of a proprietorship. Another question deals with the issue of capital gains tax of a stockbroker, who sold his sole residence. One question deals with the issue of recognition of loss for a stolen diamond ring, given that it was not insured, and that it had different cost and fair market value. Another question deals with the issue of claim amortization of leasehold improvements of a retail store.